Child DNA methylation in a randomised controlled trial of a video-feedback intervention to promote positive parenting and sensitive discipline (VIPP-SD) - Braithwaite, Elizabeth C.; Cole, Jessica; Murgatroyd, Christopher; Wright, Nicky; O’Farrelly, Christine; Barker, Beth; Ramchandani, Paul (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction A major modifiable risk factor for behavioural difficulties is harsh and insensitive parenting, and it has been hypothesised that the biological mechanism by which parenting influences child behaviour is via changes in the child's DNA methylation. We attempted to, in part, address the hypothesis that parenting is associated with child DNA methylation and, in turn, behaviour. Methods Primary caregivers of young children with behavioural difficulties (children aged 12–36 months) were randomised to receive a video-feedback Intervention to promote Positive Parenting and Sensitive Discipline (VIPP-SD) (n = 151), or usual care (n = 149). Child buccal samples were collected at a 2-year post-randomisation follow up (children aged 3–5 years, VIPP-SD group n = 106, usual care group n = 117) and were assessed for DNA methylation at the NR3C1, FKBP5 and OXYR genes. Child behaviour was assessed at baseline, post-intervention and 2-years post-randomisation using the Preschool Parental Account of Children's Symptoms (PPACS). We examined group differences in DNA methylation, associations of DNA methylation with behaviour, and sex differences. Results For the NR3C1 and OXYR genes, there were no group differences, sex differences, or associations of DNA methylation with child behaviour, though all non-significant findings were in the hypothesised direction. For FKBP5 DNA methylation, there was a significant interaction between group and sex, such that males in the usual care group had higher DNA methylation than females, but in the intervention group females had higher DNA methylation than males. However, FKBP5 DNA methylation was not associated with behaviour in males or females. Discussion We provide the first evidence from a randomised controlled trial focused on improving parenting for sex-specific changes in child DNA methylation at a key gene involved in stress reactivity and psychopathology. This study adds to our understanding of causal mechanisms linking parenting with child behaviour, which is important for developing targeted interventions. A key limitation is that child DNA methylation was only assessed at one time point, so we were unable to assess change in DNA methylation over time. However, we demonstrate that is possible to collect and analyse DNA samples from families with young children receiving parenting interventions in the community, providing impetus for further research on this topic.